Decline of HPV infections in Scandinavian cervical screening populations after introduction of HPV vaccination programs. Issue 26 (18th June 2018) - Dillner, Joakim; Nygård, Mari; Munk, Christian; Hortlund, Maria; Hansen, Bo T.; Lagheden, Camilla; Liaw, Kai-Li; Kjaer, Susanne K.
Highlights: Studies used cervical screening to monitor changes in HPV infection in populations. Populations with organized HPV vaccination programs saw drops in HPV vaccine types. Significant declines in HPV positivity were seen in the 18–26 age group. Both the low-risk HPV6/11 and the high-risk 16/18 vaccine types had declines. Abstract: Objective: To monitor the changes in prevalence of human papillomavirus (HPV) infections in women <50 years of age, participating in cervical screening programs of Denmark, Norway, and Sweden, before and after introduction of quadrivalent HPV (qHPV) vaccination. Methods: Liquid-based cytology samples were collected from 6538 women who attended cervical screening in Denmark, Norway, and Sweden in 2006–2008 and from 6332 similarly enrolled women in 2012–2013. Denmark started organized qHPV vaccination in 2008, Norway in 2009, and Sweden in 2012. All HPV testing and genotyping was performed using identical enrollment and analysis methods, by accredited general primer polymerase chain reaction methods with typing using the Luminex system. Results: Overall HPV positivity declined slightly from 36.5% in 2006–2008 to 34.5% in 2012–2013. The decline was most pronounced among women 18–26 years of age: from 54.4% to 48.1% ( P < 0.001). The decline was substantial for vaccine HPV types (HPV6/11/16/18: decline from 22.3% to 16.6%; P < 0.001) and was seen for both low-risk vaccine types (HPV6/11 declined from 5.0% to 2.5%) and high-risk vaccine types (HPV16/18 declined from 18.9% to 14.9%). Among women 27–50 years of age, there was no change between the time periods (22.5% and 21.6%, respectively). The significant decline in the younger age group was different in the 3 countries. Conclusion: This population-based study enrolling >12, 000 women participating in cervical screening in the 3 Nordic countries before and after introduction of organized qHPV vaccination demonstrated a marked decline in HPV infection in the younger population in the 2 countries where qHPV vaccination programs started in 2008–2009, suggesting that organized HPV vaccination programs resulted in a decrease of HPV types circulating in the general population.